Dampak Kegiatan Festival Anak Sholeh terhadap Pengembangan Spiritual dan Moral Anak pada Pengabdian Masyarakat di Desa Lubuk Cemara - Irwan S; Aufa Rahma Hilya; Alifiya Naura; Fadia Azzahra; Riswan Pasaribu (CV. Alim's Publishing, 2026)
This research aims to analyze the influence of the Festival Anak Sholeh activities on the spiritual and moral growth of children in community service in Lubuk Cemara Village. The Festival of Pious Children is an event designed to instill religious values thru various competitions and activities such as the Adhan competition, memorization of short surahs, and Islamic speeches. The methods used in this study were observation, interviews, and document analysis during the festival. The research findings indicate that children's participation in this festival has a positive and significant impact on enhancing their spiritual understanding and shaping moral attitudes in accordance with Islamic teachings. Children not only showed increased confidence and enthusiasm in worship but also experienced character strengthening thanks to the religious values instilled during the activity. The Sholeh Children's Festival also helps in shaping a younger generation that better understands the importance of religious moderation and social values in community life. Thus, the Festival Anak Sholeh is an effective means of children's spiritual and moral development thru sustainable community service in Lubuk Cemara Village